2011
DOI: 10.5483/bmbrep.2011.44.7.478
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Foxe1 by HR suppresses Msx1 expression in the hair follicles of HrHpmice

Abstract: Hairless (HR), a transcriptional cofactor, is highly expressed in the skin and brain. To characterize the effects of HR expression in the skin, we examined its capacity for transcriptional regulation of its target genes in mouse skin and keratinocytes. We found that Foxe1 mRNA expression was suppressed in HR-overexpressing skin, as well as in HR-expressing keratinocytes. In turn, Msx1 expression was downregulated contingent on Foxe1 downregulation in skin and keratinocytes. We also found that expression of Sfr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…HOXC13 is essential for proper hair shaft differentiation in humans 30 . Human MSX1 is expressed in the epidermis and HF, and its expression can be down-regulated in HFs by suppressing the hairless gene 31 , 32 . FOXN1 plays an important role in controlling mouse HF keratinocyte differentiation 33 .…”
Section: Discussionmentioning
confidence: 99%
“…HOXC13 is essential for proper hair shaft differentiation in humans 30 . Human MSX1 is expressed in the epidermis and HF, and its expression can be down-regulated in HFs by suppressing the hairless gene 31 , 32 . FOXN1 plays an important role in controlling mouse HF keratinocyte differentiation 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows: [ 1 ] the study must adopt a case-control design; [ 2 ] the study evaluated the relationship between rs965513, rs944289 or rs1867277 polymorphism and thyroid cancer; [ 3 ] the study provided the number of rs965513, rs944289 or rs1867277genotypes or provided sufficient data to calculate the number of rs965513, rs944289 or rs1867277 genotypes; [ 4 ] the study provided an Odds Ratio (OR) with 95% Confidential Interval (CI) as well as the P value or the study provided sufficient data to calculate the OR and 95% CI [ 5 ] at least 10 patients entered; [ 6 ] no lapping data was included.…”
Section: Methodsmentioning
confidence: 99%
“…For further classification, differentiated thyroid cancer including papillary thyroid carcinoma and follictalar thyroid carcinoma, in which papillary thyroid carcinoma accounts for 75% in thyroid cancer [ 1 3 ]. In the past few years, these polymorphisms (rs965513, rs944289 and rs1867277) in the Forkhead factor E1(FOXE1) region and differentiated thyroid cancer (DTC) risk had been independently researched by subsequent studies [ 4 6 ]. The results and conclusions of these studies had been influenced by the use of different insufficient power, ethnic, phenotypic heterogeneity and small effect of the polymorphism on thyroid cancer risk and.…”
Section: Introductionmentioning
confidence: 99%
“…161 Moreover, in the Hairpoor mouse (a mouse model for hereditary hypotrichosis), the absence of Foxe1 in skin and keratinocytes results in downregulation of Msx expression. 162 Hhex Hhex (formerly known as Hex for Hematopoietically Expressed Homeobox or Prh for Proline-rich Homeobox) is a homeodomain-containing transcription factor that was first identified in multipotent hematopoietic cells. It was successively demonstrated that Hhex is expressed in other tissues including the thyroid.…”
Section: Foxe1mentioning
confidence: 99%